Life Cycle Assessment of Greenhouse Gases for Milk Production: A Review - Mohini, Madhu; Gupta, Shiva; Datt, Chander; Mondal, Goutam (Indian Journal of Animal Nutrition, 2018)
In India, dairy sector has important impacts on the economy and ecosystem services and contributes to essential societal needs for food. Economic survey (2015-16) noted that India ranks first in milk production with an annual output of 146.3 million tonnes with a growth of 6.26% during 2014-15 accounting for 18.5% of world milk production. Whereas, FAO (2014) reported a 3.1% increase in world milk production from 765 million tonnes in the year 2013 to 789 million tonnes in the year 2014. The per capita availability of milk in India has increased from 176 g/d in the year 1990-91 to 322 g/d by 2014-15 which was more than the world average of 294 g/d during the year 2013. This represents a sustained growth in availability of milk and milk products for the growing population. As the public concern about climate change and environmental sustainability continues to grow and societal pressures on the dairy industry to reduce its environmental impact are rising, therefore, the concept of life cycle assessment (LCA) of GHG emissions for milk production helps in quantifying the environmental impact of dairy sector and furnishing a method of identifying mitigation options suited to reduce those environmental burdens. The process of LCA is generally composed of 4 components including goal and scope, life cycle inventory (LCI) analysis, life cycle impact assessment and interpretation. Creating an LCI of emissions to the environment (e.g. GHG emissions) for an animal agricultural system such as dairy sector, is challenging. The diversity of management systems across operations and segments of the dairy sector contribute to the challenges of creating LCI analyses. The purpose of this article was to assess the current LCA methodologies being used in analysis of the dairy sector and to compare the complexity and variations among LCA studies. It is also emphasised that more of such studies are required under different livestock rearing systems for different species under different agro-climatic zones of India.